Mixplanting pubescent and glabrous cassava affects abundance of Typhlodromalus aripo and its prey mite Mononychellus tanajoa - Onzo, A.; Hanna, R.; Toko, M. (Wiley, 2014)
There is an increasing awareness that vegetation diversity can affect herbi-vore and natural enemy abundance and that plants can play a major rolein directly manipulating natural enemy abundance for protection againstherbivore attacks. Using data from cassava fields, we aimed at (i) testingthe capacity of the predatory miteTyphlodromalus aripoto control the her-bivorous miteMononychellus tanajoain a chemical exclusion trial; and (ii)testing, based on the differential preference byT. aripofor cassava culti-vars, how combinations of two morphologically different cassava cultivarswith differential suitability to the predator can improve its populationdensities on the non-favourable cultivar, thereby reducingM. tanajoaden-sities with subsequent increases in cassava yield. The study was conductedin a cassava field in Benin, West Africa. The experiments confirmed thatT. aripoeffectively suppressesM. tanajoapopulations on both cultivarsand showed, in the no-predator-exclusion experiments, that cultivar com-binations have significant effects onM. tanajoaandT. aripodensities.Indeed,T. aripoload on the non-preferred cultivar was lowest in subplotswhere the proportion ofT. aripo-preferred cultivar was also low, while,and as expected,M. tanajoaload on the non-preferred cultivar showeddecreasing trends with increasingT. aripodensities. The possible mecha-nisms by which cultivar mixing could increase predator load on the non-favourable cultivar were discussed. Our data showed that appropriatecultivar combinations effectively compensate for morphologically relateddifferences in natural enemy abundance on a normally predator-deficientcultivar, resulting in lower pest densities on the non-favourable cultivar.In practical terms, this strategy could, in part, enhance adoption of culti-vars that do not support sufficient levels of natural enemies for pest con-trol.